Cowpea Genotypic Variations in N2 Fixation, Water Use Efficiency (δ13C), and Grain Yield in Response to Bradyrhizobium Inoculation in the Field, Measured Using Xylem N Solutes, 15N, and 13C Natural Abundance - Mohammed, Mustapha; Mbah, Glory C.; Sowley, Elias N. K.; Dakora, Felix D. (Frontiers in Agronomy, 2022)
To evaluate cowpea genotypic differences in response to inoculation with Bradyrhizobium sp. strains BR 3267 and CB756 in the field, 15 genotypes were assessed for N2 fixation using 15N natural abundance and assays of xylem N solutes (ureides, nitrates and amino-N). Carbon isotope discrimination (δ13C) was used as a surrogate for water use efficiency, and grain yield determined at maturity. Within each location, the tested cowpeas elicited contrasting responses to inoculation with either Bradyrhizobium strains. For example, inoculating Apagbaala and IT90K-277-2 with strain BR 3267 doubled N-fixed and grain yield at Nyankpala when compared to inoculation of the same genotypes with strain CB756, whereas the inoculation of Padituya with strain CB756 increased those same parameters relative to non-inoculation. Similar contrasting results were also obtained at Savelugu and Gbalahi, where bacterial inoculation with each strain resulted in up to 5-folds increase in N-fixed and 4-folds increase in grain yield depending on the cowpea/inoculant combinations used and the planting location. The main effect of genotype showed that the percent N derived from N2 fixation (%Ndfa) by the test cowpeas ranged between 74.4 – 89.8%, 11.7 – 50.5% and 71.9 – 90.3% at Nyankpala, Savelugu and Gbalahi, respectively. The genotypes grown at Savelugu generally exhibited low %Ndfa which was augmented by greater soil N uptake leading to grain yield increases, a finding supported by significant positive correlations when N-fixed and N content were each plotted against grain yield within locations. The inverse relationship between symbiosis and soil N uptake was also supported by negative correlations between xylem nitrate concentration and relative ureide N abundance (RU-N), and between xylem nitrate concentration and %Ndfa measured from 15N natural abundance. Some high yielding genotypes also elicited greater water use efficiency (δ13C), a trait that could be exploited for increased cowpea production in water limiting environments. This study demonstrates the presence of genotypic differences in cowpea response to inoculation in the field, and contributes to the literature regarding the factors influencing legume inoculation response in the tropics.